Perinatal characteristics and outcome of preterm singleton, twin and triplet infants in NSW and the ACT, Australia (1994–2005). Issue 1 (10th August 2009) - Garg, P; Abdel-Latif, M E; Bolisetty, S; Bajuk, B; Vincent, T; Lui, K
Abstract : Objective: To compare the perinatal characteristics, neonatal morbidity and mortality of preterm singletons, twins and triplets born at 22–31 weeks' gestation and admitted to neonatal intensive care units (NICU) in New South Wales and Australian Capital Territory between 1994 and 2005. Methods: Perinatal characteristics and neonatal outcome data were obtained from the regional NICUS data collection to test for a priori hypothesis. The 10 068 very premature infants studied included 7304 (72.5%) singletons, 2444 (24.2%) twins and 320 (3.2%) triplets. Results: Assisted conception was associated with a higher maternal age and increased twins and triplets admissions into NICU than spontaneous conceptions (twins OR 6.9, 95% CI 6.1 to 8.0; and triplets OR 35.6, 95% CI 27.6 to 45.8). Major neonatal morbidities were similar between the three groups of singletons, twins or triplets. While twins of 22–27 weeks' gestation (adjusted OR 1.39, 95% CI 1.12to 1.72) had higher mortality compared with singletons, mortality only diverged below 24 weeks' gestation. Mortality was predicted by decreasing gestational age, male gender and lack of antenatal steroids, whereas assisted conception was protective against mortality (adjusted OR 0.69, 95% CI 0.57 to 0.86). Conclusions: Assisted conception contributed to higher very premature NICU admissions of twins and triplets. Preterm twins at the very extreme of viability had higher mortality compared with singletons. The protective effect of assisted conception against mortality requires further research.